Comparison of the Effects of Prophylactic and Therapeutic Administrations on Peripheral Neuropathy in Streptozotocin-Diabetic Rats with Gliclazide or Methylcobalamin - Yao, Hongping; Feng, Juanyi; Zheng, Qiaowei; Wei, Youxia; Yang, Guangde; Feng, Weiyi (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objective To observe the differences in curative effects between prophylactic and therapeutic administrations of Gliclazide (GLZ) or Methylcobalamin (MCA) on diabetic peripheral neuropathy in rats.Methods GLZ (25 mg/kg/day) or MCA (175 μg/kg/day) was orally administrated prophylactically to streptozotocin-induced diabetic rats for 8 weeks before diabetic peripheral neuropathy developed or administrated therapeutically after diabetic peripheral neuropathy developed, respectively. The motor nerve conduction velocities (MNCV), aldose reductase (AR) activities, the polyol contents and antioxidative enzyme activities in the sciatic never tissues were determined. The morphology of sciatic never tissues was observed.Results In comparison to vehicle, most of the changes in the sciatic nerves of the diabetic rats (e. g., delayed MNCV, altered/damaged nerve structure, enhanced AR activity, increased polyol contents, altered Cu, Zn-superoxide dismutase, glutathione-peroxidase activities, and elevated malondialdehyde level) were significantly ameliorated by prophylactic administration with either GLZ or MCA. In contrast, only few of above-mentioned parameters were alleviated in DPN rats by therapeutic administration with GLZ or MCA as compared to vehicle. The curative effects of GLZ or MCA prophylactic administration on MNCV, AR activity, polyol contents and antioxidative enzyme activities were markedly stronger than therapeutic administration.Conclusion Prophylactic administration of GLZ or MCA was superior to the therapeutic administration in alleviation of diabetic neuropathy in STZ-rats, suggesting that pharmacotherapy should be initiated at a much earlier stage before diabetic neuropathy developed, but not at a later stage after never damage reached.
Keywords: diabetic peripheral neuropathy; prophylactic administration; therapeutic administration